Evaluating the Impact of Drilling Fluids on Well Integrity and Environmental Compliance: A Comprehensive Study of Offshore and Onshore Drilling Operations - Kenneth, Effam (Journal of Science & Technology, 2020)
The current work explores the importance of drilling fluids in the provision of well integrity together with compliance with the environment in offshore and onshore rig operations. Through case studies of the Erha, Otuo South and Ogbele fields, this research demonstrates that current management practices such as tank management, use of solid control equipments and compliance with calibration procedures are effective and that safety and environmental management standards are being met. This study utilizes results from AAR and periodic facility integrity check and recommends both as crucial feedback tools for future drilling fluid management. Research evidence shows that good fluid management processes play an important role in well stability and lesser effects on environment however, there are issues encountered with offshore and onshore fields. Ideas for improvement of these practices are made, and it is emphasized that it is crucial to aim at the constant enhancement of the existing operating procedures to facilitate effective and efficient drilling.
Keywords: Drilling fluids; well integrity; environmental compliance; offshore drilling; onshore drilling